Profiles and predictors of mental health of university students in Hong Kong under the COVID-19 pandemic - Shek, Daniel T. L.; Chai, Wenyu; Li, Xiang; Dou, Diya (Frontiers in Psychology, 2023)
This study investigated the mental health problems of university students in Hong Kong and related sociodemographic and psychosocial predictors under the pandemic. A total of 978 undergraduate students (mean age = 20.69±1.61) completed an online questionnaire measuring sociodemographic factors, psychological morbidity, positive well-being, COVID-19 related stress and self-efficacy, and positive psychosocial attributes. Psychosocial risk factors included psychological morbidity, COVID-19 related stress, and difficulties encountered under the pandemic, whereas protective factors comprised pandemic related self-efficacy, positive psychological attributes, positive environmental factors, need satisfaction and positive perception towards service. Results showed that psychological morbidity in the participants was widespread, and it was related to sociodemographic factors, particularly family financial difficulties. While pandemic related stress positively predicted psychological morbidity and negatively predicted well-being indicators, COVID-19 self-efficacy showed an opposite effect. Besides, positive psychological attributes (resilience, emotional competence, and positive beliefs related to adversity) and environmental factors (healthy family functioning, peer support, and supportive community atmosphere) negatively predicted psychological morbidity and positively predicted well-being. Furthermore, need satisfaction and positive perception towards service were negatively associated with psychological morbidity and positively associated with well-being, while perceived difficulties showed an opposite effect.